2010
DOI: 10.1016/j.athoracsur.2010.04.070
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Awake Videothoracoscopic Surgery on Postoperative Lymphocyte Responses

Abstract: Background. Surgical stress and general anesthesia can have detrimental effects on postoperative immune function. We sought to comparatively evaluate postoperative lymphocytes response in patients undergoing videoassisted thoracoscopic surgery (VATS) under thoracic epidural or general anesthesia.Methods. Between October 2008 and June 2009, 50 patients with nonmalignant pulmonary conditions were randomized to undergo VATS through either sole epidural anesthesia and spontaneous ventilation (awake group, n ‫؍‬ 25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
76
1
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 104 publications
(81 citation statements)
references
References 35 publications
0
76
1
4
Order By: Relevance
“…He used the term "neutrophillymphocyte stress factor" to express the ratio of neutrophils to lymphocytes, and this ratio can be routinely used in clinical intensive care unit practice. Some authors recommend that the patient remain awake during surgery versus general anesthesia to reduce the postoperative lymphocyte response [9,10]. The postoperative lymphocyte percentage was higher in patients with postoperative infection compared to the other group in our study (9.0% vs. 7.43%, respectively), but this difference was not statistically significant.…”
Section: Discussioncontrasting
confidence: 51%
“…He used the term "neutrophillymphocyte stress factor" to express the ratio of neutrophils to lymphocytes, and this ratio can be routinely used in clinical intensive care unit practice. Some authors recommend that the patient remain awake during surgery versus general anesthesia to reduce the postoperative lymphocyte response [9,10]. The postoperative lymphocyte percentage was higher in patients with postoperative infection compared to the other group in our study (9.0% vs. 7.43%, respectively), but this difference was not statistically significant.…”
Section: Discussioncontrasting
confidence: 51%
“…The possible role of better preserved anticancer immunosurveillance is also to be further evaluated, even though preliminary reports have suggested a lesser impairment in perioperative immune and hormonal status (53,54).…”
Section: Long-term Outcomesmentioning
confidence: 99%
“…It has been suggested that immune response is better preserved after VATS compared to thoracotomy (65)(66)(67). Our recent studies showed that the same effects of lower immunological suppression and reduced inflammatory response can be detected when comparing uniVATS and multiport VATS (68).…”
Section: The Recent Progressmentioning
confidence: 53%